Penerapan Metode Multi Games Dalam Pembelajaran Mufrodat Di LKP Ibnu Khaldun Driyorejo Gresik - Sholihudin Al-Ayyubi (Program Studi Pendidikan Agama Islam, 2021)
This article is the result of a study that describes the stages in the application of the multigames method in Arabic mufradat learning by adding vocabulary intensely to each meeting. LKP Ibnu Khaldun is an Arabic language development institution by applying the multigames method which refers to an independent guidebook entitled